The Tort of Malicious Prosecution: A Principled Account - Law-Smith, Michael (McGill Law Journal / Revue de droit de McGill, 2024)
This article provides a justification for the often-criticized tort of malicious prosecution. It begins by discussing the Supreme Court of Canada’s malicious prosecution caselaw and by reconstructing the Court’s expressed policy-based account of the tort. This policy-based account raises three concerns: (1) it renders the malice standard arbitrary, (2) it fails to explain why malicious prosecutors should be held accountable as a matter of private rather than public law, and (3) it leaves the source of the plaintiff’s private right mysterious. However, the Court’s jurisprudence supports a more principled account, specifically one that focuses on the nature and limits of a prosecutor’s public office. This office-based account responds to the above concerns while affirming the Court’s view that malice is the correct standard of fault and, more generally, that malicious prosecution is a distinctly private wrong.